Formulation And Organoleptic Test of Herbal Red Ginger Syrup (Zingiber Officinale Variertas Rubrum) as A Health Drink - Iriyanti, Sri; Irianti, Dian; Masrif, Masrif; Sri Rahayu, Endah; Kristanto, Budi (Universitas Aisyah Pringsewu, 2024)
Red ginger can be processed into an alternative herbal drink for the community. In the manufacturing process, cinnamon, lemongrass, granulated sugar and other spices can be added to make syrup. This red ginger syrup tastes sweet, spicy and contains antioxidants that are good for health. A heating technique has been developed in the process of making red ginger syrup. This research aims to determine the manufacture of red ginger syrup, the organoleptic properties of the color, aroma, taste and viscosity of red ginger syrup as well as the hedonic test of the label on the ginger syrup container. The type of research used was an experimental method with a one-shot case study design using 3 different formulas with variations in the amount of red ginger and granulated sugar. The research involved 18 trained panelists to carry out organoleptic tests using a hedonic scale. The study found that 61.11% of red ginger syrup panelists preferred formula 3, 50% preferred formula 2, and 44.44% preferred formula 1. The majority preferred Formula 2, with 55.55% preferring it. The viscosity test showed similar opinions across the three formulas. Plastic bottles were preferred 50% of the time. The results of the preference test for containers showed that panelists preferred plastic bottle containers with 50% of panelists choosing to like them. The conclusion of this research is that there is no difference in the level of preference (color, aroma, taste, texture) of panelists regarding the organoleptic properties of red ginger syrup.